2018
DOI: 10.1002/ab.21752
|View full text |Cite
|
Sign up to set email alerts
|

Association between intimate partner violence during pregnancy and maternal pregnancy complications among recently delivered women in Bangladesh

Abstract: Intimate partner violence (IPV), an actual or threatened physical, sexual, or psychological abuse by a current or former partner or spouse, is a common global public health issue. Understanding both the prevalence of IPV during pregnancy and its potential impact on the health of pregnant women is important for the development and implementation of interventions to prevent maternal morbidity and mortality. The purpose of this study was to explore the association between maternal experiences of IPV during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
2
20
0
1
Order By: Relevance
“…Studies indicated that domestic violence exerts a negative impact on the physical and psychological health of women [33]. Violence during pregnancy increases the risk of obstetric complications [34]. Moreover, physiological stress, anxiety and depression of abused women lead to lower utilization of maternity care and poor nutrition during pregnancy that may eventually result in premature birth or low birth weight babies [35].…”
Section: Plos Onementioning
confidence: 99%
“…Studies indicated that domestic violence exerts a negative impact on the physical and psychological health of women [33]. Violence during pregnancy increases the risk of obstetric complications [34]. Moreover, physiological stress, anxiety and depression of abused women lead to lower utilization of maternity care and poor nutrition during pregnancy that may eventually result in premature birth or low birth weight babies [35].…”
Section: Plos Onementioning
confidence: 99%
“…Although not associated with IPV in the multivariate model, a significantly higher proportion of the IPV cohort was pregnant at the time of the index visit when compared with the control group. The prevalence of violence during pregnancy is known to be high (affecting up to 20% of women) (30), and IPV is associated with obstetric complications (31), postpartum depression (32), and maternal homicide (33)(34)(35).…”
Section: Imaging Findingsmentioning
confidence: 99%
“…The South-East Asian region, primarily Bangladesh, India, Myanmar, Sri Lanka, Thailand, and Timor-Leste, was also found to have the highest median prevalence of intimate partner homicide among all female fatalities totaling to nearly 55% [ 5 ]. Women in Bangladesh who experienced sexual IPV during pregnancy were also at an increased risk of suffering from medical, obstetric or multifaceted complications during pregnancy [ 12 ]. However, there is a literature gap in identifying the most vulnerable cohorts of women who suffer from IPV in Bangladesh and its subsequent effect on miscarriages, induced abortions and stillbirths.…”
Section: Introductionmentioning
confidence: 99%